FIGURE 2. Camptocercus streletskayae Smirnov, 1998 in Morphology and phylogenetic position of three species of genus Camptocercus Baird, 1843 (Cladocera: Anomopoda: Chydoridae) - Sinev, Artem Y. (Zenodo, 2015)
FIGURE 2. Camptocercus streletskayae Smirnov, 1998, parthenogenetic female from Russia, Chukotka, a puddle in the region of the Anadyr River. A–B, labrum. C–M, thoracic limbs. C, limb I. D, IDL of limb I. E–F, limb II. G, exopodite of limb III. H– I, inner portion of limb III. J, exopodite of limb IV. K–L, inner portion of limb IV. M, limb V. Published as part of Sinev, Artem Y., 2015, Morphology and phylogenetic position of three species of genus Camptocercus Baird, 1843 (Cladocera: Anomopoda: Chydoridae), pp. 169-186 in Zootaxa 4040 (2) on page 173, DOI:10.11646/zootaxa.4040.2.4, http://zenodo.org/record/233695